(untitled) (Italian Journal of Public Health, 2005)
In 1991 the publication of the Harvard Medical Practice Study gave a new light to the problem of patient safety. Because of its rigorous methodology, its dimensions (more than 30,000 clinical records from 51 hospitals) and number and variety of the departments involved (medicine, surgeries, emergence, etc) the Harvard study represents a milestone in the patient safety research. It unequivocally demonstrated that errors happen in the hospitals, they can be life-threatening and most of them are preventable. A wide number of other reports have followed the Harvard study, most of them refer to hospitals while the rate of errors in primary care is less known.These more recent studies represent an important progress because the Harvard study is considered old in its approach describing errors as the result of negligence or misconduct and missing totally the problems of the medical environment (the system approach).